The Best Australian Science Writing 2012. - Finkel, Elizabeth (University of New South Wales Press, 2013)
How were Ned Kelly's bones finally identified? What makes cockroaches some of the most successful creatures on the planet? Could some obscure bacteria finally rid the world of dengue fever? How did infant reflux become the disease of the moment? From the furthest reaches of the universe to the microscopic world of our genes, science offers writers the kind of scope other subjects simply can't match. Good writing about science can be moving, funny, exhilarating, or poetic, but it will always be honest, rigorous, and true to the research that underlies it. This volume showcases the nation.